2012
DOI: 10.1099/vir.0.043919-0
|View full text |Cite
|
Sign up to set email alerts
|

Replication-dependent downregulation of cellular angiotensin-converting enzyme 2 protein expression by human coronavirus NL63

Abstract: Like severe acute respiratory syndrome coronavirus (SARS-CoV), human coronavirus (HCoV)-NL63 employs angiotensin-converting enzyme 2 (ACE2) as a receptor for cellular entry. SARSCoV infection causes robust downregulation of cellular ACE2 expression levels and it has been suggested that the SARS-CoV effect on ACE2 is involved in the severity of disease. We investigated whether cellular ACE2 downregulation occurs at optimal replication conditions of HCoV-NL63 infection. The expression of the homologue of ACE2, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 39 publications
2
116
0
7
Order By: Relevance
“…Furthermore, in contrast to HCoV-NL63 infection, SARS-CoV infection results in a marked downregulation of ACE2 expression on the cell surface, thereby disrupting RAS homeostasis; this in itself may cause severe lung injury (20). Dijkman et al showed that ACE2 expression was downregulated upon HCoV-NL63 infection although the result was heavily dependent upon the infection efficiency (52). Based on these reports, one wonders whether ACE2 is actually the cellular receptor for HCoV-NL63.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in contrast to HCoV-NL63 infection, SARS-CoV infection results in a marked downregulation of ACE2 expression on the cell surface, thereby disrupting RAS homeostasis; this in itself may cause severe lung injury (20). Dijkman et al showed that ACE2 expression was downregulated upon HCoV-NL63 infection although the result was heavily dependent upon the infection efficiency (52). Based on these reports, one wonders whether ACE2 is actually the cellular receptor for HCoV-NL63.…”
Section: Discussionmentioning
confidence: 99%
“…45 Continued viral infection and replication contribute to reduced membrane ACE2 expression, at least in vitro in cultured cells. 46 Down-regulation of ACE2 activity in the lungs facilitates the initial neutrophil infiltration in response to bacterial endotoxin 47 and may result in unopposed angiotensin II accumulation and local RAAS activation. Indeed, in experimental mouse models, exposure to SARS-CoV-1 spike protein induced acute lung injury, which is limited by RAAS blockade.…”
Section: P Otential For Benefit R Ather Than Harm Of R a A S Blockersmentioning
confidence: 99%
“…SARS-CoV2, SARS-CoV, and HCoV-NL63, a virus that causes a mild respiratory infection, are all known to employ ACE2 as a receptor (3,4,16,17). Given the functions of ACE2 in the cardiovascular system, the importance of angiotensin-directed pharmacology in cardiovascular disease and the apparent propensity for severe illness among patients with COVID-19 with cardiovascular comorbidity, the ACE2 molecule has been the subject of much attention (18).…”
Section: Pathogenesis: Angiotensin-converting Enzymementioning
confidence: 99%